Karakteristik antibodi anti Ganoderma sp. yang dihasilkan dengan menggunakan jenis dan sumber antigen yang berbeda [Characteristic of antibodies againt Ganoderma sp produced from different types and sources of antigens] - Irma KRESNAWATY; Kholis A AUDAH; Hasim MUNAWAR; Happy WIDIASTUTI (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2017)
Basal stem rot (BSR) disease caused by Ganoderma sp. is the most important disease in oil palm plantations.The effectivity of BSR control depends on early detection of this disease. The earlier the disease is known, the severity of damage could be prevented. Therefore, technology for early detection of Ganoderma infection is very important. Immunochromatographic techniques based on the reaction of antigens and antibodies can be developed for detection of Ganoderma sp infection. The objective of the study was to produce antibodies using different Ganoderma sp. In this study, immunoglobulin Y ( IgY ) against Ganoderma sp produced in chicken eggs was used as the source of antibodies. Laying hens were immunized with several types of Ganoderma sp. because it is known to have genetic variations. The source of Ganoderma sp. isolates were mycelium and exudates. The polyclonal IgY antibodies produced economically and abundantly. The antibodies derived from the mycelium showed more consistent results compared with those derived from the exudates. In addition, the antibodies derived from Ganoderma sp of Cimulang and Bekri showed higher reactivity with some of the antigens compared to those from Cisalak Baru (CSB). The characteristics and the protein profiles of antibodies produced using Cimulang, Bekri and Cisalak Baru isolates were vary in term of, sensitivity and amino acid compositions